Editorial: time to eat? Skipping breakfast in metabolic‐associated fatty liver disease—Authors' reply. Issue 4 (28th January 2022) - Xie, Jiarong; Xu, Lei; Xu, Chengfu
LINKED CONTENT: This article is linked to Xie et al papers. To view these articles, visit https://doi.org/10.1111/apt.16727 and https://doi.org/10.1111/apt.16755